Critical History Monographs and Intersectionality in Social Studies: A Case From Enslavement. (2nd January 2021) - James-Gallaway, ArCasia D.
Abstract : With a focus on methods courses, this article makes a case for social studies teacher educators to employ in their pedagogy an intersectional perspective. I ask social studies teacher educators to consider critical history monographs, specialized book-length studies that center on marginalized perspectives, as pedagogical tools that complement primary sources. Elevating scholarship on enslaved females in the U.S., I highlight affordances and the utility of intersectionality as a generative analytic for use in social studies methods courses. I illustrate how social studies teacher educators can better prepare their students to teach from an intersectional perspective that more fully humanizes multiply oppressed peoples in U.S. history. This discussion has implications for secondary social studies, teacher education, and history education.